Internasionalisasi Kurikulum Berbasis ACTFL dan CEFR: Peluang, Tantangan, dan Implementasi dalam Pendidikan Bahasa Arab di Indonesia - Maulida, Siti Nur Adzkia (Maliki Interdisciplinary Journal, 2026)
The internationalization of the Arabic language education curriculum in Indonesia has become an urgent necessity to enhance graduates' competitiveness at the global level. However, aligning the local curriculum with international standards such as the American Council on the Teaching of Foreign Languages (ACTFL) and the Common European Framework of Reference for Languages (CEFR) continues to face various structural and methodological challenges. This study aims to identify the opportunities, challenges, and implementation strategies of these two standards within the context of Arabic language education in Indonesia. This research employs a library research method by analyzing curriculum documents, educational policies, and relevant academic literature concerning the integration of ACTFL and CEFR. The findings indicate that the adoption of ACTFL and CEFR offers significant opportunities for establishing adaptive, objective, and globally recognized language competency standards. Nevertheless, several challenges remain, including teachers' pedagogical readiness, the limited availability of contextualized teaching materials, and resistance to changes in traditional curricula. As a solution, effective implementation requires a gradual reconstruction of curriculum design, intensive professional development for educators, and the development of assessment instruments aligned with these international standards. This alignment is expected to transform Arabic language education in Indonesia into a more practical system oriented toward global communicative competence.